The relationship between obesity and plasma level of factor V and fibrinogen - Jabber, Halla A.; Alsaidissa, Jaffar N.; Al-Rubaie, Haithem A. (Journal of the Faculty of Medicine Baghdad, 2017)
Background:  Obesity is a medical condition in which excess body fat has accumulated to the extent that it has an adverse effect on health. . It measured by BMI (body mass index), obesity is considered when the BMI is ≥ 30 kg/m2. It increases the risk of coronary heart disease, Diabetes Mellitus and Cancer. Chronic inflammation and impaired fibrinolysis in obesity may induce thrombosis.Aim of study: assess the effect of BMI (body mass index) on plasma level of Factor V and fibrinogen in obese and normal weight subjects.Methods: This study was started on December 2015 and completed on June 2016, and included 51 obese attended alyarmouk Teaching Hospital. As well 25 non-obese subjects, were recruited as a control, age range  from18to 50 years old .The hemostatic parameters done for them included the prothrombin time, activated partial thromboplastin time, FV activity, fibrinogen level, and platelet count.Results: There were insignificant difference in the means of prothrombine time (PT),activated partial thromboplastine time(aPTT), Factor V activity( FV)  and Platelet count (PLT)of obese group compared to control  group with P value (0.63, 0.902, 0.44, 0.484) respectively. There was significant difference in  the mean  of fibrinogen of obese group compared to control  group with P value (0.006).The correlation between BMI and (PT, PLT, FV and fibrinogen)in obese and control study groups were statistically  insignificant with (P > 0.05)  , but a significant positive correlation between BMI and PTT in obese group was found with  (P=0.037). There was a significant negative correlation between FV and PT in obese and control groups (P =0.001).There was insignificant positive correlation between fibrinogen and PT in obese and control groups (P > 0.05).  Conclusions: Significant difference in the mean of plasma level of fibrinogen concentration between obese group and normal weight group was found. Insignificant difference in the means of PT, aPTT, platelet count and FV activity between obese group and normal weight group were found.